A Case Report: Building communities with training and resources for Open Science trainers - Brinken, Helene; Kuchma, Iryna; Kalaitzi, Vasso; Davidson, Joy; Pontika, Nancy; Cancellieri, Matteo; Correia, Antónia; Carvalho, José; Melero, Remedios; Kastelic, Damjana; Borba, Filomena; Lenaki, Katerina; et al. (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2019)
To foster responsible research and innovation, research communities, institutions, and funders are shifting their practices and requirements towards Open Science. Open Science skills are becoming increasingly essential for researchers. Indeed general awareness of Open Science has grown among EU researchers, but the practical adoption can be further improved. Recognizing a gap between the needed and the provided training offer, the FOSTER project offers practical guidance and training to help researchers learn how to open up their research within a particular domain or research environment.Aiming for a sustainable approach, FOSTER focused on strengthening the Open Science training capacity by establishing and supporting a community of trainers. The creation of an Open Science training handbook was a first step towards bringing together trainers to share their experiences and to create an open and living knowledge resource. A subsequent series of train-the-trainer bootcamps helped trainers to find inspiration, improve their skills and to intensify exchange within a peer group. Four trainers, who attended one of the bootcamps, contributed a case study on their experiences and how they rolled out Open Science training within their own institutions.On its platform the project provides a range of online courses and resources to learn about key Open Science topics. FOSTER awards users gamification badges when completing courses in order to provide incentives and rewards, and to spur them on to even greater achievements in learning.The paper at hand describes FOSTER Plus’ training strategies, shares the lessons learnt and provides guidance on how to reuse the project’s materials and training approaches.